Impact of stellar variability on exoplanet detectability and characterisation - Meunier, Nadège (Comptes Rendus. Physique)
Stellar variability has become a major issue to detect low mass planets using the radial velocity technique. I present the approaches followed to characterise the amplitude and the properties of stellar variability in radial velocity. More specifically, the approach consisting in using our knowledge of the Sun to understand better the different processes which are occuring at different scales proved to be very useful. This has been done in different ways, based on observations and models. This is crucial because it is then possible to compare disk-integrated radial velocities with actual structures on the solar surface, such as spots and plages, and with photospheric flows at different spatial scales. Many physical processes indeed affect the radial velocity measurements: they are mostly due to magnetic features (spots and plages), flows (oscillations, granulation, supergranulation, meridional flows), and to the interactions between magnetic fields and flows (inhibition of the convective blueshift in plages). I present in more detail a selection of studies aiming at characterising the impact of stellar variability, in particular the relationship between activity indicators and radial velocities, and then focusing on mass characterisation and detection performance. Finally, I briefly review the impact of stellar variability on photometric transits and astrometry, which are also affected, but to a lesser extent.